Evaluation of Blood Requisition Forms Submitted to Transfusion Medicine Department of a Tertiary Care Hospital in Dhaka, Bangladesh - Biswas, Daanish Arefin; Wasim, Md; Bhuiyan, Hasiba Akhter; Nabi, Quazi Md Rashid Un (Sir Salimullah Medical College Journal, 2022)
Introduction: Blood requisition form (BRF) analysis is one of the most efficient and effective approaches to assess and monitor rational use of blood and its product. BRF is the first line of communication between the clinicians and transfusion medicine specialists which helps to recognize and evaluate inappropriate use of blood. This issue is frequently underrated by the clinicians which results in increased risk of inappropriate transfusion. The current study is aimed to examine the pattern of completion of blood requisition forms and to ensure safe blood transfusion. Materials and methods: This cross sectional prospective study was conducted from January 2020 to December 2021, at the Department of Transfusion Medicine, Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh. A total of 32,133 blood requisition forms that were submitted during the study period were compiled and reviewed anonymously. The data were analyzed using Microsoft Excel. Results: During the study period, a total of 32,133 Blood requisition forms were analyzed. Only 15.2% of these forms were duly completed. Rest of the forms had one or more important parameters left blank. The most common incomplete BRF items were the clinical history or differential diagnosis of the patient (52.66%), presumed date and time of transfusion (95.19%), previous transfusion history (95.9%), and referring doctor’s name and designation (88%). Blood requests were more for females (52.02%) than males (47.98%) during the period. Requisitions were more for adults (90%) than pediatric patients. Conclusion: The current study provides evidence that the rate of completion of BRFs is not satisfactory. The request forms evaluated were not covering acceptable demographic and clinical data of the patients. Both the Hospital Transfusion Committee (HTC) and the Department of Transfusion Medicine can help to improve and standardize transfusion practice by working together. Sir Salimullah Med Coll J 2022; 30: 142-147